Growing Trend of Generation Z of Pakistan for Exchange/Scholarship Programs and Impact on Their Employability Status: An Analysis of Erasmus Mundus, UGRAD and Fulbright in the Light of Human, Social Capital and Transformative Learning Theories - Fatima, Hira (Pakistan Journal of Humanities and Social Sciences, 2025)
The main focus of this study is to analyze the growing interest of the Generation Z of Pakistan in foreign exchange and scholarship programs such as Rasmus Mundus, UGRAD and scholarship program, Fulbright, and then evaluate their employability back him. Statistical data, reports and comments have been collected from the primary sources of data available with these programs on their websites and addresses. The study, then, compares the global statistics with that of Pakistani statistics covering participating trends and the results regarding jobs. To achieve better results, the research has been designed to utilize mixed method and application of three main theoretical perspectives; human capital of Becker, and Coleman, social capital of Bourdieu and Transformative learning of Mezirow. The findings of the analysis of the available statistics and data indicate that there is equally same average trend among the global and Pakistan Generation Z. It also becomes apparent that employability opportunities with good skills acquired in these programs such as adaptation, acculturation and other transferable soft skills have increased manifolds including wage average in the market. It also suggests that for pragmatic measures to be recommended, a longitudinal study including qualitative analysis of the impressions of alumni on a vast scale is required. However, the study has proved that the Generation Z of Pakistan is fully aware of the capital and social value of these programs and is hellbent on acquiring them as shown by the average increase in the trends of the successful students.